Calculated plasma volume status and outcomes in patients undergoing transcatheter aortic valve replacement. (5th March 2021) - Shimura, Tetsuro; Yamamoto, Masanori; Yamaguchi, Ryo; Adachi, Yuya; Sago, Mitsuru; Tsunaki, Tatsuya; Kagase, Ai; Koyama, Yutaka; Otsuka, Toshiaki; Yashima, Fumiaki; Tada, Norio; Naganuma, Toru; et al.
Abstract: Aims: This study investigated the prognostic value of plasma volume status (PVS) in patients who underwent transcatheter aortic valve replacement (TAVR). Methods and results: Plasma volume status was calculated in 2588 patients who underwent TAVR using data from the Japanese multicentre registry. All‐cause mortality and heart failure hospitalization (HFH) within 2 years of TAVR were compared among the PVS quartiles (Q1, PVS < 5.5%; Q2, PVS 5.5–13.5%; Q3, PVS 13.5–21.0%; and Q4, PVS ≥ 21.0%). Subgroups were stratified by the PVS cut‐off value combined with the New York Heart Association (NYHA) class as follows: low PVS with NYHA I/II ( n = 959), low PVS with NYHA III/IV ( n = 845), high PVS with NYHA I/II ( n = 308), and high PVS with NYHA III/IV ( n = 476). The cumulative all‐cause mortality and HFH within 2 years of TAVR significantly increased with increasing PVS quartiles [8.5%, 16.8%, 19.2%, and 27.0% ( P < 0.001) and 5.8%, 8.7%, 10.3%, and 12.9% ( P < 0.001), respectively]. The high‐PVS group regardless of the NYHA class had a higher all‐cause mortality and HFH [9.6%, 18.2%, 24.5%, and 30.4% ( P < 0.001) and 6.1%, 10.4%, 14.1%, and 11.3% ( P < 0.001)]. In a Cox regression multivariate analysis, the PVS values of Q3 and Q4 had independently increased all‐cause mortality [hazard ratio (HR), 1.50 and 1.64 ( P = 0.017 and P = 0.008), respectively], and Q4 had independently increased HFH (HR, 1.98, P = 0.005). The low PVS with NYHA III/IV, high PVS with NYHA I/II, and high PVS with NYHA III/IV also had significantly increased all‐cause mortality [HR, 1.45, 1.73, and 1.86 ( P = 0.006, P = 0.002, and P < 0.001), respectively] and HFH [HR, 1.52, 2.21, and 1.70 ( P = 0.049, P = 0.002, and P = 0.031), respectively]. Conclusions: Plasma volume status is useful for predicting all‐cause mortality and HFH after TAVR.